IMPLEMENTASI METODE WAFA DALAM MENINGKATKAN HASIL BELAJAR TAHSIN DAN TAHFIDZ - Ervin Nurkhalizah; Akil Akil; Agus Susanto (Tarbiyatuna Kajian Pendidikan Islam, 2024)
The aim of this research is to find out how the Wafa Method is used to teach Tahsin and Tahfidz Al-Qur'an at SMPIT Harapan Umat Karawang. Another aim of this research is to find out how well the results of learning to read the Koran using tajwid rules are. This research uses a qualitative approach, which allows further explanation of the problem to be studied naturally. Researchers considered the idea of the Wafa method, which seeks to help students read the Qur'an. To collect and obtain data, researchers use methods such as observation, interviews, and documentation. Qualitative-descriptive analysis is used to process data. This data comes from documentation, interviews and observations carried out by researchers both before and after the implementation of the learning. According to the results of data analysis, research using the Wafa Method in Improving Tahsin and Tahfidz Learning Outcomes at SMPIT Harapan Umat Karawang really requires careful and systematic planning, implementation and supervision/evaluation. The Wafa method has proven effective in improving tahsin and tahfidz learning outcomes at SMPIT Harapan Umat Karawang. This can be seen from student achievement, ability to read and write the Al-Qur'an, memorize the Al-Qur'an, as well as motivation, student interest in the Al-Qur'an and the achievement of tahsin tahfidz learning results can be seen from the students' grades and tasnif results. at SMPIT Harapan Umat Karawang.